Application of textured YBCO bulks with artificial holes for superconducting magnetic bearing. (18th May 2015) - Dias, D H N; Sotelo, G G; Moysés, L A; Telles, L G T; Bernstein, P; Kenfaui, D; Aburas, M; Chaud, X; Noudem, J G
Abstract: The levitation force between a superconductor and a permanent magnet has been investigated for the development of superconducting magnetic bearings (SMBs). Depending on the proposed application, the SMBs can be arranged with two kinds of symmetries: rotational or linear. The SMBs present passive operation, low level of noise and no friction, but they need a cooling system for their operation. Nowadays the cooling problem may be easily solved by the use of a commercial cryocooler. The levitation force of SMBs is directly related to the quality of the superconductor material (which depends on its critical current density) and the permanent magnet arrangement. Also, research about the YBa2 Cu3 O x (Y123) bulk materials has shown that artificial holes enhance the superconducting properties, in particular the magnetic trapped field. In this context, this work proposes the investigation of the levitation force of a bulk Y123 sample with multiple holes and the comparison of its performances with those of conventional plain Y123 superconductors.